PERBEDAAN MEDIA TANAM MEMPENGARUHI PERTUMBUHAN ANAKAN STROBERI (PISAH RUMPUN) PADA SISTEM HIDROPONIK FERTIGASI TETES - Fany Juliarti Panjaitan; Onesimus Ke Lele; Putri Ahmadiana Hasanah; Desak Ketut Tri Martini (JURNAL AGRISA, 2025)
The growing medium is a crucial component that determines the success of plant growth and development, particularly in hydroponic cultivation systems, which rely heavily on the physical and chemical conditions of the medium. Selecting the right growing medium plays a role in providing optimal mechanical support, aeration, and water and nutrient retention capacity for plants. This study aimed to analyze the effect of different growing media types on the growth of hydroponically cultivated strawberry seedlings. The study was conducted using a randomized block design with one treatment factor, namely the growing medium type. The treatments tested consisted of Carbonized rice husk (SB), cocopeat (CP), and a combination of carbonized rice husk and cocopeat (SBC) with certain compositions. The growth parameters observed included the number of leaves, root length, plant height, and the number of productive shoots. The results showed that the use of a growing medium mixture of burnt rice husks and cocopeat with a ratio of 1:3 provided the best results for several growth variables. This treatment resulted in an average number of leaves of 9.86 and a root length of 16.7 cm, which was statistically significantly different compared to other growing media treatments. These findings indicate that the combination of media provides optimal rooting conditions, particularly in terms of aeration and water-holding capacity. However, differences in growing media type did not significantly impact plant height and the number of productive shoots. Therefore, it can be concluded that growing media selectively influences certain growth components in hydroponic strawberries.